Konsep Sedekah Dalam Perspektif Pendidikan Islam: Studi Analisis Isi Buku The Power Of Sedekah - Paslah, Roni; Amirudin, noor; muyasaroh (Jurnal Mahasiswa Pendidikan, 2021)
This research is a type of library research that uses the object of literature review and the primary data source is the book The Power Of Sedekah by Lu'lu' Mawaddah and the secondary sources are taken from related books, journals, articles. with research. The data analysis technique is to use descriptive and content analysis (content analysis). The purpose of this study is to explain and identify Lu'lu' Mawaddah's thoughts on the concept of alms in the perspective of Islamic Education. In the results of the research that can be obtained by the author, in general Lu'lu' Mawaddah's thought is that Islamic education is here as the intended tool while the concept of alms focuses on humans and in this case, of course, the way to achieve the goals of Islamic education itself is to truly really understand human nature, because humans are here as subjects.